Effect of broad-spectrum parenteral antibiotics on composition of intestinal microflora of humans. - Giuliano, M (1987)
We compared the effects of four beta-lactam drugs with widely differing antibacterial and pharmacological properties on the composition of the intestinal flora. Cefoxitin, piperacillin, cefoperazone, and aztreonam were given intravenously for 9 days to healthy volunteers. Cefoperazone reduced the numbers of aerobic and anaerobic bacteria to undetectable levels. At the other extreme, cefoxitin had little effect on the normal flora. Aztreonam markedly reduced the numbers of aerobes, whereas piperacillin had a variable effect on both aerobic and anaerobic bacteria. There was extensive overgrowth of enterococci in subjects given cefoxitin or aztreonam, which have little activity against this species, and of yeasts in subjects given cefoperazone or piperacillin. Cefoperazone reached concentrations of 2,727 to 8,840 micrograms/g in the feces, whereas the other agents were generally undetectable. These results show that the new beta-lactam antibiotics produce widely varying effects on the fecal microflora after parenteral administration and that these effects are consistent with the antibacterial and pharmacological properties of the drugs.